2017
DOI: 10.3393/ac.2017.33.4.146
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal Perforation After Anorectal Manometry for Low Anterior Resection Syndrome

Abstract: We experienced 3 cases of manometry-induced colon perforation. A 75-year-old man (case 1) underwent anorectal manometry (ARM) 3 years after radiotherapy for prostate cancer and a laparoscopic intersphincteric resection for rectal cancer. A 70-year-old man (case 2) underwent ARM 3 months after conventional neoadjuvant chemoradiotherapy and a laparoscopic low anterior resection for rectal cancer. A 78-year-old man (case 3) underwent ARM 2 months after a laparoscopic intersphincteric resection for rectal cancer. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…Indeed, our manometric data showed that the decreased percentage of MRP was significantly higher in the RAIR‐absent group compared with the RAIR‐present group (data not shown). More importantly, in order to avoid neorectal perforation, Lee et al have suggested that the manometric examination should be performed 2 months or longer after sphincter‐preserving surgery [30].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, our manometric data showed that the decreased percentage of MRP was significantly higher in the RAIR‐absent group compared with the RAIR‐present group (data not shown). More importantly, in order to avoid neorectal perforation, Lee et al have suggested that the manometric examination should be performed 2 months or longer after sphincter‐preserving surgery [30].…”
Section: Discussionmentioning
confidence: 99%
“…However, the presence of profuse bleeding, advanced age, presence of comorbidities and sepsis are predictors of poor prognosis in these cases [7] , [9] , [14] , [15] , [16] . In general, perforation secondary to non-traumatic causes is more frequent, being predominantly due to colorectal cancer, ischemia, diverticulitis, inflammatory bowel disease, inadequate use of enema, iatrogenic endoscopy or anorectal manometry or fecal impaction [6] , [7] , [9] , [10] , [11] , [12] , [13] , [14] . Favorable prognostic factors for a satisfactory outcome in both traumatic and non-traumatic causes are early initiation of surgery and care in a specialized surgical center [6] , [12] .…”
Section: Discussionmentioning
confidence: 99%
“…Favorable prognostic factors for a satisfactory outcome in both traumatic and non-traumatic causes are early initiation of surgery and care in a specialized surgical center [6] , [12] . The unfavorable prognostic factors are advanced age, requirement of mechanical ventilation, prolonged stay in hospital and intensive care unit, APACHE II (Acute Physiology and Chronic Health Evaluation II) score between 8 and 30, SOFA (Sequential Organ Failure Assessment) score between 0 and 12, DIC (Disseminated Intravascular Coagulation) score between 0 and 8, POSSUM (Physiological and Operative Severity Score for the Enumeration of Mortality and Morbidity) score between 34 and 74, CT (Computerized Tomography) dirty mass volume in cm 3 (234 ± 211), presence of profuse bleeding, use of conservative treatment, performance of primary anastomosis without a diverting stoma, ASA Grade 3, 4 or 5, chronic steroid use, serum creatinine level > 3.0 mg/dL, disseminated cancer, white blood cell count <3500/mL, low preoperative systolic blood pressure and Hinchey classification IV [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] . Dirty mass is a little-known concept that represents the finding of focal collection of extraluminal fecal matter [19] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations